2013
DOI: 10.3109/10715762.2013.814912
|View full text |Cite|
|
Sign up to set email alerts
|

Quercetin treatment against ischemia/reperfusion injury in rat corpus cavernosum tissue: a role on apoptosis and oxidative stress

Abstract: Reactive oxygen metabolites play an important role in the ischemia/reperfusion (I/R)-induced tissue injury. This study was designed to investigate the possible protective effects of quercetin against I/R injury of the rat corpus cavernosum tissue. To induce I/R injury, abdominal aorta was clamped for 30 min and reperfused for 60 min. Quercetin (20 mg/kg) or vehicle was given before ischemia and just after reperfusion in the I/R group and in the sham-operated control group in which clamping was not performed. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…DOX-induced toxicity stimulates the translocation of calreticulin to the cell surface in tumor cells, enhancing uptake and clearance by dendritic cells (Bines et al 1996). Both in vitro and in vivo data support the hypothesis that a combination of the antioxidant Quercetin (QR) and DOX produces beneficial, synergistic effects in the treatment of breast cancer and leukemia (Black et al 2002;Bolzan et al 1997;Ceballos et al 1992) However, exposure of pregnant women to chemotherapy results in congenital malformations in as many as 10-20 % of cases (Cevik et al 2013).…”
Section: Introductionmentioning
confidence: 81%
“…DOX-induced toxicity stimulates the translocation of calreticulin to the cell surface in tumor cells, enhancing uptake and clearance by dendritic cells (Bines et al 1996). Both in vitro and in vivo data support the hypothesis that a combination of the antioxidant Quercetin (QR) and DOX produces beneficial, synergistic effects in the treatment of breast cancer and leukemia (Black et al 2002;Bolzan et al 1997;Ceballos et al 1992) However, exposure of pregnant women to chemotherapy results in congenital malformations in as many as 10-20 % of cases (Cevik et al 2013).…”
Section: Introductionmentioning
confidence: 81%
“…Quercetin has been reported to inhibit oxidative damage in various I/R models and tissues, including myocardial, testicular and corpus cavernosum, but there are no studies against the I/R induced bladder injury . In our previous studies we have demonstrated the protective effects of quercetin (QT) against spinal cord injury‐induced bladder and I/R‐induced corpus cavernosum tissue damage and apoptosis, and suggested that this protection is through its antioxidant, anti‐apoptotic and anti‐inflammatory properties . Thus in the present study, we investigated the effect of QT on the I/R injury in the rat bladder first time in the literature, to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 86%
“…In the sham‐operated control group, the abdominal aorta was left intact and the rats were treated with vehicle. The rationale for QT dose was based on previous studies showing anti‐oxidant effects of QT . At the end of the reperfusion period, 1 h after the second dose of s/c quercetin, rats were decapitated to obtain bladder tissue samples for in vitro organ bath experiments, biochemical analyses and histological examination.…”
Section: Methodsmentioning
confidence: 99%
“…According to previous studies, quercetin (QE) is a powerful antioxidant agent with the ability to reduce tissue damage after I/R processes 891011. Resveratrol (RSV) is found in many plants, particularly grapes and peanuts.…”
Section: Introductionmentioning
confidence: 99%